The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1152/ajpcell.00245.2014
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor inhibition protects against ischemic acute kidney injury in mice

Abstract: Activation of the purinergic P2X7 receptor (P2X7R) has been associated with the development of experimental nephritis and diabetic and hypertensive nephropathy. However, its role in acute kidney injury (AKI) remains unknown. In this study, we examined the effects of P2X7R inhibition in a murine model of ischemia-reperfusion (I/R)-induced AKI using A438079, a selective inhibitor of P2X7R. At 24 h after I/R, mice developed renal dysfunction and renal tubular damage, which was accompanied by elevated expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 47 publications
5
48
0
Order By: Relevance
“…This finding suggests that A438079 also has other unspecified effects during the priming. Indeed, a recent study has shown that treatment with A438079 inhibits ERK1/2 phosphorylation [40]. Since NF-κB is required for the synthesis of NLRP3 induced by LPS [38], inhibition of ERK (upstream of NF-κB [41]) may reduce the expression of NLRP3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests that A438079 also has other unspecified effects during the priming. Indeed, a recent study has shown that treatment with A438079 inhibits ERK1/2 phosphorylation [40]. Since NF-κB is required for the synthesis of NLRP3 induced by LPS [38], inhibition of ERK (upstream of NF-κB [41]) may reduce the expression of NLRP3.…”
Section: Discussionmentioning
confidence: 99%
“…LPS-induced ALI model was created as described previously [9]. Male C57BL/6 mice (8-9 weeks of age) were anesthetized with intraperitoneal International Immunopharmacology 27 (2015) [38][39][40][41][42][43][44][45] ketamine (80 mg/kg) and xylazine (15 mg/kg). 6 mg/kg of LPS (Sigma-Aldrich, St. Louis, MO, USA) was delivered in 50 μl of phosphatebuffered saline (PBS) to the lungs via a 20-gauge angiocath catheter used as an endotracheal tube.…”
Section: Lps-induced Acute Lung Injury (Ali) Modelmentioning
confidence: 99%
“…Exposure of endothelial cells to oxidative stress results in the activation of signalling molecules, such as extracellular signal‐regulated kinases (ERKs), which regulate cell survival and proliferation in differentiated cells. For example, phosphorylation of ERK1/2, a well‐studied signalling molecule in different cell types, including endothelial cells, activates downstream signalling molecules and induces cell proliferation . In addition, ERK1/2 is an upstream activator of an estimated 50 nuclear factors and proteins that affect cell differentiation, proliferation and stress responses, as well as promoting tumour growth, including ETS domain‐containing protein ELK1, nuclear factor (NF)‐κB, inducible nitric oxide synthase, c‐Myc and heat shock transcription factor‐1.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the specific P2X7 receptor antagonism used in this study, A437089, has been satisfactory used in different preclinical models of inflammation in the periphery3334353637. A438079 has been found to be CNS permeable, and its treatment reduced seizure severity during status epilepticus, as well as dopamine depletion in a model of Parkinson’s disease6970.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, A438079 is a selective competitive antagonist for the human and rodent P2X7 receptor with good bioavailability and CNS penetration widely used in preclinical animal models of disease3132. A438079 reduces inflammation in models of colitis, ischemic acute kidney injury, contact dermatitis, and liver injury and fibrosis3334353637.…”
mentioning
confidence: 99%